Protective/detoxicative function of metallothionein in the rat brain and blood induced by controlled cadmium doses - Shiyntum, H. N.; UshakovаG. A. (Regulatory Mechanisms in Biosystems, 2015)
Cadmiumclassified as a major carcinogen is considered a poisonous and unwanted heavy metal to a lot of tissues in many organisms. Of many publications already available, the general consensus is that the cadmium attenuating element is metallothionein (MT) through its interchangeable mechanism with Zn triggered by the presence of Cd, providing binding sites for Cd ions. MT was first discovered in the kidney cortex of the horse; it represents a low molecular weight protein, rich in cysteine residues which effectively bind with metals. Its functions consist in detoxification of heavy metals like mercury, arsenic, cadmium, homeostasis of essential metals including copper and zinc, anti-oxidation against reactive oxygen species, protection against DNA damage, oxidative stress, cell survival, angiogenesis, apoptosis, and increase of proliferation. In this work, we sought to highlight the protective function of MT in the brain and serum of rats by means of detoxification under induced effects of controlled Cd doses. We have done this by exposing Wistar rats to Cd at different doses in drinking water at different time intervals. In two independent experiments, 58 rats were subjected to 0.1 or 1.0 µg Cd2+/kg of body weight for 15 or 36 days under different conditions. The obtained data indicates the different functioning systems for the brain and the blood for MT metabolism under Cd effect. Our results indicate significant loss of metallothionein level in the brain and important increases in the amount of MT in serum proving that even minimal ingestion of toxic Cd is enough to trigger the release of MT protein in blood.